ANALISIS SEMIOTIKA CHARLES S. PIERCE TERHADAP IKLAN POLITIK JOKOWI-MA'RUF DAN PRABOWO-SANDI - Thibbur Ruhany (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The 2019 election is so special, apart from the rising political temperature in Indonesia, the elections is also like a rematch of the 2014 elections that brought together two strong candidates, Joko Widodo and Prabowo Subianto as presidential candidates. Each candidate collides with ideas to win public sympathy and influence voter behavior through political advertising. This study will examine the ideas of Jokowi and Prabowo's government through political advertising. The advertisement that will be used as the main analytical material in this paper is political advertising on social media through the Youtube platform, namely the Sarjana Kerja Kerja Kerja! and the advertisement of Arwah si Manis Jembatan Ancur. Findings suggest that in packaging the ideas related to their campaign programs, each candidate has different communication styles and approaches. Sarjana Kerja Kerja Kerja! contains criticism of Indonesia Kerja slogan. This advertisement conveys reality criticism that is not in accordance with Jokowi's Nawacita expectations and offers solutions to changes in the economic system, prosperous, and independent Indonesia. Whereas through the political campaign si Manis Jembatan Ancur, a message was found on the success of infrastructure development in the Jokowi era which was not only focused on big cities but also to remote villages as illustrated in the background of the advertisement. In this advertisement there is a campaign content where one of them is the figure of cleric who has many similarities with Jokowi's vice-presidential candidate, K.H. Ma'ruf Amin is synonymous with santri. Key Words; Semiotics, Sanders Pierce, Political Campaign, Jokowi Prabowo